Characterization of Dye-decolorizing Peroxidase (DyP) from Thermomonospora curvata Reveals Unique Catalytic Properties of A-type DyPs - Chen, Chao (J Biol Chem, 2015)
Dye-decolorizing peroxidases (DyPs) comprise a new family of heme peroxidases, which has received much attention due to their potential applications in lignin degradation. A new DyP from Thermomonospora curvata (TcDyP) was identified and characterized. Unlike other A-type enzymes, TcDyP is highly active toward a wide range of substrates including model lignin compounds, in which the catalytic efficiency with ABTS (k(cat)(app)/K(m)(app) = (1.7 × 10(7)) m(−1) s(−1)) is close to that of fungal DyPs. Stopped-flow spectroscopy was employed to elucidate the transient intermediates as well as the catalytic cycle involving wild-type (wt) and mutant TcDyPs. Although residues Asp(220) and Arg(327) are found necessary for compound I formation, His(312) is proposed to play roles in compound II reduction. Transient kinetics of hydroquinone (HQ) oxidation by wt-TcDyP showed that conversion of the compound II to resting state is a rate-limiting step, which will explain the contradictory observation made with the aspartate mutants of A-type DyPs. Moreover, replacement of His(312) and Arg(327) has significant effects on the oligomerization and redox potential (E°′) of the enzyme. Both mutants were found to promote the formation of dimeric state and to shift E°′ to a more negative potential. Not only do these results reveal the unique catalytic property of the A-type DyPs, but they will also facilitate the development of these enzymes as lignin degraders.